2020
DOI: 10.1016/j.cobeha.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gambling advertising and gambling attitudes, intentions and behaviours: a critical and meta-analytic review

Abstract: The relationship between gambling advertising and 2 gambling attitudes, intentions and behaviours: 3 a critical and meta-analytic review 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…The harmful effects of gambling and associated advertising have been suggested to extend beyond populations of disordered gamblers and are apparent across the entire harm-spectrum; including children and young people [ 3 , 14 , 15 ]. Comparable to previously conducted reviews of alcohol and tobacco [ 16 , 17 ], two recently published systematic reviews [ 18 , 19 ] and one narrative review [ 20 ] have indicated that gambling advertising is facilitative of induced gambling intentions or cravings, increased participation and riskier (more impulsive) betting. However, these reviews also identify many of the methodological gaps within the existing gambling advertising research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The harmful effects of gambling and associated advertising have been suggested to extend beyond populations of disordered gamblers and are apparent across the entire harm-spectrum; including children and young people [ 3 , 14 , 15 ]. Comparable to previously conducted reviews of alcohol and tobacco [ 16 , 17 ], two recently published systematic reviews [ 18 , 19 ] and one narrative review [ 20 ] have indicated that gambling advertising is facilitative of induced gambling intentions or cravings, increased participation and riskier (more impulsive) betting. However, these reviews also identify many of the methodological gaps within the existing gambling advertising research.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical concentration upon disordered gamblers may pathologize the issue of gambling-harm induced by advertising. This may draw attention away from advertising-induced harm experienced by low-moderate risk gamblers [ 18 ]. Furthermore, the self-reported effects of gambling advertising are often hindered by recall and self-report bias.…”
Section: Introductionmentioning
confidence: 99%
“…Marketing on social media has also created a new dimension in the way gambling products are promoted 7,8 . A recent critical and meta‐analytic review of gambling advertising suggested there was a positive association between exposure to gambling advertising and gambling‐related attitudes, and intentions and behaviours in adults 9 . However, to our knowledge, there has been no such research with young people.…”
mentioning
confidence: 98%
“…The media have long adopted images of masculinity in the promotion of gambling, alcohol, and tobacco use, but the capacity of the new media to shape peer norms is greater than ever before. 5 A pernicious accentuation of peer norms 6 is perpetuating outdated stereotypes of what it is to be a man. For these reasons there have been growing calls for the inclusion of boys and young men in policies to counter gender inequalities in health and wellbeing outcomes 7 across media and marketing, in education, and in community settings including sport.…”
Section: Gender Norms and The Mental Health Of Boys And Young Menmentioning
confidence: 99%